The Evidence Behind the Treatment of Canine Idiopathic Epilepsy - Marios Charalambous; David Brodbelt; Holger Andreas Volk (Veterinary Evidence, 2016)
Oral phenobarbital and imepitoin in particular, followed by potassium bromide and levetiracetam are likely to be effective for the treatment of canine idiopathic epilepsy. There is strong evidence supporting the use of oral phenobarbital and imepitoin as ‘first line’ medications. However, there remains a lack of evidence for targeted treatment for the various individual epileptic phenotypes and quite limited evidence on direct comparisons of the efficacy between various anti-epileptic drugs.